2011
DOI: 10.1111/j.1439-0531.2010.01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mSOF and G1.1/G2.2 Media on the Developmental Competence of SCNT‐Derived Bovine Embryos

Abstract: The objective of this study was to compare the effect of two culture media: modified synthetic oviductal fluid (mSOF) and G1.2/G2.2, on the developmental competence of bovine somatic cell-cloned embryos. Cloned embryos were produced by transferring adult skin fibroblasts into enucleated MII oocytes. After activation, the reconstructed embryos were randomly allotted to either mSOF or G1.2/G2.2 for culture (the embryos were transferred from G1.2 to G2.2 on days 3 of culture). The development competence of cloned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 34 publications
2
28
0
2
Order By: Relevance
“…Therefore, sequential media may theoretically be more optimal for culture of developing embryos than single culture medium. Commercially available sequential media have been widely for embryo culture in various species and have shown better competence to support development of IVF embryos both in vitro and in vivo than single culture media in some previous studies [1,3,8] . In addition, some studies showed that a medium cultured for long periods of time can rapidly deteriorate, resulting in its inability to support embryo development [1,4,16] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, sequential media may theoretically be more optimal for culture of developing embryos than single culture medium. Commercially available sequential media have been widely for embryo culture in various species and have shown better competence to support development of IVF embryos both in vitro and in vivo than single culture media in some previous studies [1,3,8] . In addition, some studies showed that a medium cultured for long periods of time can rapidly deteriorate, resulting in its inability to support embryo development [1,4,16] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies showed that a medium cultured for long periods of time can rapidly deteriorate, resulting in its inability to support embryo development [1,4,16] . Sequential culture media formulated for in vitro development of mammalian embryos overcome this problem [8,16] . Currently, there are different sequential media available for culturing mammalian embryos such as G1/G2 [8,21] , Quinn's Advantage sequential medium and Sydney IVF medium [5,7] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations